Radiolabeled silicon-rhodamines as bimodal PET/SPECT-NIR imaging agents - Kanagasundaram, Thines; Laube, Markus; Wodtke, Johanna; Kramer, Carsten Sven; Stadlbauer, Sven; Pietzsch, Jens; Kopka, Klaus (Pharmaceuticals, 2021)
Radiolabeled fluorescent dyes are decisive for bimodal imaging as well as highly in demand for nuclear- and optical imaging. Silicon-rhodamines (SiRs) show unique near-infrared (NIR) optical properties, large quantum yields and extinction coefficients as well as high photostability. Here, we describe the synthesis, characterization and radiolabeling of novel NIR absorbing and emitting fluorophores from the silicon-rhodamine family for use in optical imaging (OI) combined with positron emission tomography (PET) or single photon emission computed tomography (SPECT), respectively. The presented photostable SiRs were characterized using NMR-, UV-Vis-NIR-spectroscopy and mass spectrometry. Moreover, the radiolabeling conditions using fluorine-18 or iodine-123 were extensively explored. After optimization, the radiofluorinated NIR imaging agents were obtained with radiochemical conversions (RCC) up to 70% and isolated radiochemical yields (RCY) up to 54% at molar activities of g.t. 70 GBq/µmol. Radioiodination delivered RCCs over 92% and allowed to isolate the 123I-labeled product in RCY of 54% at a molar activity of g.t. 7.6 TBq/µmol. The radiofluorinated SiRs exhibit in vitro stabilities g.t. 70% after two hours in human serum. The first described radiolabeled SiRs are a promising step toward their further development as multimodal PET/SPECT-NIR imaging agents for planning and subsequent imaging-guided oncological surgery.
Gesehen am 07.01.2022